Curvas de crescimento de características de carcaça obtidas por ultrassonografia em bovinos Nelore selecionados para peso pós desmame - Coutinho, Carolina Cesarino [UNESP] (2014)
The purpose of this study was to evaluate the effect of selection for postweaning weight parameters in growth curves of growth and carcass traits. Records of 2404 Nellore animals from three selection lines were analyzed: two selection lines for high postweaning weight (NeS and NeT), Selection Nellore (NeS) and Traditional Nellore (NeT), and a control line (NeC), in which animals are selected for the mean weight. The measurements were performed: body weight (BW), hip height (ALT), Longissimus muscle area (AOL), back fat thickness (EGL) and rump fat thickness (EGG). Records were collected from 8 to 20 months of age for males and 11 after 26 months of age for females. The parameters A (asymptotic value) and k (growth rate) were estimated by technique of nonlinear models using NLIN procedure of SAS, that included fixed effect of herd (NeS NeT and NeC) in the model, with the objective of evaluate differences in the estimated parameters in different herds. The selected animals (NES and NeT) showed higher growth rate than control herd (NEC) for all traits. Herd effect on curves parameters was significant (<0,001) for PC, ALT and AOL in males, and females for EGS and EGG. Selection for postweaning weight was effective in altering growth curves, resulting in animals with greater growth potential.